Effective treatment of early triple-negative breast cancer in a patient with sickle cell disease through chemotherapy and immune checkpoint inhibitor therapy: The keynote 522 regimen - Froessl, Luise Josefine; Saxon-Filipe, Stevany; Rambally, Siayareh; Syed, Samira (Current problems in cancer. Case reports, 2025)
Hemoglobin SS (Hb SS) disease is a genetic condition leading to acute and chronic complications in all organ systems. There is limited data on cancer treatment outcomes in this population. This case report presents a woman in her mid-40 s with Hb SS disease and early-stage triple-negative breast cancer (TNBC), treated successfully with the Keynote 522 regimen combining chemotherapy (paclitaxel, carboplatin, doxorubicin and cyclophosphamide) and pembrolizumab. Despite potential risks, the patient tolerated therapy well with no sickle cell crises and only expected moderate side effects. This case demonstrates the feasibility of aggressive cancer treatment in patients with Hb SS disease when managed with close multidisciplinary care, though more research is needed on immunotherapy safety in this group.